Relationship between Spiritual Intelligence and Competencies of Thai Professional Accountants - Woenthong, Somsri (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The purpose of this research is to study the relationship between spiritual intelligence and competencies of Thai professional accountants, Questionnaires data were collected from 401 Thai professional accountants who attended the training with the Federation of Accounting Professions by random and convenience sampling. This research used partial least squares structural equation modeling (PLS-SEM) to analyze the relationship between spiritual intelligence and competencies of Thai professional accountants through the mediating role of self-efficacy and job satisfaction. The results showed that spiritual intelligence has a relationship with competencies of Thai professional accountants, which can be explained by the role of self-efficacy and job satisfaction. Moreover, the analysis supported a positive relationship between competencies of Thai professional accountants and job performance. All results are statistically significant at the 0.01 level Article history : Received 8 August 2019 Revised 26 November 2019 Accepted 28 November 2019 SIMILARITY INDEX = 0.00